The clinical use of hypnosis in cognitive behavior therapy : a practitioner's casebook - Chapman, Robin A. (Springer Pub., 2006)
Annotation McLean Hospital, Belmont, MA. Compilation provides a theoretical framework for the integration of hypnosis with cognitive behavior therapy. Presents evidence-based research and case examples of treatment methods used for conditions such as anger, anxiety, depression, and post-traumatic stress disorder. For practitioners. Softcover.